Becoming a Project Leader Blending Planning, Agility, Resilience, and Collaboration to Deliver Successful Projects - Laufer, Alexander (Springer International Publishing, 2018)
This book blends academic rigor and real world experience on the agile and planning schools of project management and the process of becoming a project leader. To some, project management is all about logically and rationally planning out dependencies and mapping them out into a flawless plan; a plan that must be rigorously and undeviatingly followed in all its geometric perfection. To others it is about agility - 15 minute scrum meetings and responding on the fly to the unpredictable exigencies that the randomness of the living, breathing world throws up. In reality, smart project leaders do both. They understand that you can't deliver a project if you make an "either/or" choice between these approaches - you must do "both/and". These managers strive for stability and flexibility, they use formal and informal processes, and they function as managers and leaders. In Becoming A Project Leader the authors have applied their blend of intellectual rigor and hard-nosed practical experience to identify four concrete roles employed by successful project managers. The first three roles-planning, agility, and resilience-focus on coping with changes, with each role relating to a different kind of change. These three roles, which complement each other, can be implemented effectively only when they are supported by the fourth role, collaboration. Becoming an expert at understanding and delivering that blend requires constant reflection and interaction with peers - all part of the process of becoming a project leader. Based on years of experience, research and thinking and refined through 20 in-depth interviews with practicing project managers and senior executives, Becoming A Project Leader delivers the solution to all those blown budgets, shot schedules and disappointing deliverables. .